Transitivity Processes in King Charles III’s Speech on State Banquet with the United States: A Systemic Functional Linguistics Study - Edward Prambudi Susilo Handoko; Elvi Citraresmana; Nani Darmayanti (Universitas Cokroaminoto Palopo, 2026)
This study explores the relationship between clause structure and the social construction of meaning found in verbal speeches. Drawing on Halliday's theory of the transitivity system, particularly on the process elements which are part of the Systemic Functional Linguistics theory. This research aims to investigate the distribution of transitivity processes found in King Charles III's speech at the state banquet in 2025, welcoming the state visit of US President Donald Trump at Windsor Palace. Furthermore, using descriptive qualitative analysis, this study focuses on analyzing the functions expressed in the transitivity process theory found in the speech. The data used in this study consist of 50 clauses from King Charles' speech at the state banquet with US President Donald Trump in 2025. Moreover, this study found that six transitivity processes were identified in the research. The processes found in this study are material, relational attributive, relational identification, mental, verbal and behavioral processes. Each process plays a different role and function in the speech. All the processes present in the State Banquet speech were used by King Charles III to representing experience and constructing political discourse, strengthening diplomatic relationship by defining ideological themes like historical events, cultural and language similarities, also boosting cooperation in various fields. In conclusion, this study provides information on how linguistic structures are used by a head of state strategically employ language not only to communicate information but also to construct ideological meanings and reinforce diplomatic objectives to maintain the continuity of diplomatic relationship.